Poly (N-isopropylacrylamide) Microgel-Based Optical Devices for Sensing and Biosensing - Molla R. Islam; Andrews Ahiabu; Xue Li; Michael J. Serpe (Sensors, 2014)
Responsive polymer-based materials have found numerous applications due to their ease of synthesis and the variety of stimuli that they can be made responsive to. In this review, we highlight the group’s efforts utilizing thermoresponsive poly (N-isopropylacrylamide) (pNIPAm) microgel-based optical devices for various sensing and biosensing applications.